Direct pharmacological Akt activation rescues Alzheimer's disease like memory impairments and aberrant synaptic plasticity. (January 2018) - Yi, Jee Hyun; Baek, Soo Ji; Heo, Sunghoo; Park, Hye Jin; Kwon, Huiyoung; Lee, Seungheon; Jung, Jiwook; Park, Se Jin; Kim, Byung C.; Lee, Young Choon; Ryu, Jong Hoon; Kim, Dong Hyun
Abstract: Amyloid β (Aβ) is a key mediator for synaptic dysfunction and cognitive impairment implicated in Alzheimer's disease (AD). However, the precise mechanism of the toxic effect of Aβ is still not completely understood. Moreover, there is currently no treatment for AD. Protein kinase B (PKB, also termed Akt) is known to be aberrantly regulated in the AD brain. However, its potential function as a therapeutic target for AD-associated memory impairment has not been studied. Here, we examined the role of a direct Akt activator, SC79, in hippocampus-dependent memory impairments using Aβ-injected as well as 5XFAD AD model mice. Oligomeric Aβ injections into the 3rd ventricle caused concentration-dependent and time-dependent impairments in learning/memory and synaptic plasticity. Moreover, Aβ aberrantly regulated caspase-3, GSK-3β, and Akt signaling, which interact with each other in the hippocampus. Caspase-3 and GSK-3β inhibitor ameliorated memory impairments and synaptic deficits in Aβ-injected AD model mice. We also found that pharmacological activation of Akt rescued memory impairments and aberrant synaptic plasticity in both Aβ-treated and 5XFAD mice. These results suggest that Akt could be a therapeutic target for memory impairment observed in AD. Highlights: Oligomeric Aβ impaired learning and memory and synaptic plasticity. Caspase inhibition ameliorated Aβ-induced deficits. Akt activation ameliorated Aβ-induced deficits. GSK-3β inhibition ameliorated Aβ-induced deficits. Akt activation ameliorated learning and memory and synaptic deficits in 5XFAD mice.